(untitled) (Bangladesh Rice Journal, 2020)
A newly released drought tolerant rice variety BRRI dhan66 suitable for rainfed lowland ecosystem of Bangladesh is an improvement over existing drought tolerant rice varieties. The variety has satisfactorily been passed in the proposed variety trial conducted in the farmers’ field. As a result, National Seed Board (NSB) approved this variety for commercial cultivation in the wet season (T. Aman) in 2014. It has modern plant type with 120 cm plant height and matures in 110-115 days. The important feature of this variety is higher drought tolerance during reproductive stage. It can produce 4.5-5.0 t/ha grain yield without irrigation during reproductive stage. It can produce satisfactory yield when soil moisture remains <20% and perch water table depth is more than 70-80 cm from the surface. The seed size of the variety is 24 g with intermediate long bold grain. It has long, wide and erect flag leaf with deep green colour. It is highly promising as a drought tolerant rice variety for cultivation in the drought prone area, which helps farmers’ to get rid of huge economic loss and is contributing in sustaining food security. Bangladesh Rice j. 2019, 23(1): 45-55